Studi Eksperimental: Efektivitas AI Dalam Meningkatkan Aksesibilitas Informasi PCOS Via Mobile App - Ruth Megarini Panjaitan; Miranda Mas Tasya Sitorus; Evta Indra (LKP Unity Academy, 2025)
Polycystic Ovary Syndrome (PCOS) is a hormonal disorder commonly experienced by women of reproductive age; however, the level of literacy regarding PCOS remains relatively low. Limited access to clear and easily understandable information has contributed to a lack of awareness of this condition. This study aims to develop an Artificial Intelligence (AI)-based mobile application called OVAI as an educational medium to improve the accessibility of PCOS information. The research was conducted by distributing questionnaires to female respondents aged 18–45 years using a Likert scale. The collected data were analyzed to determine the level of user acceptance and the consistency of the research instrument. The results showed that the OVAI application was successfully developed with interactive chatbot features and user-friendly educational content. The application was considered helpful in enabling users to better understand information related to PCOS and to access information more practically. Therefore, the OVAI application can be utilized as a digital educational medium for women of reproductive age.